Bioassays of entomopathogenic microbes and nematodes. - Ascher, K. R. S.; Navon, A. (Wallingford :CABI Publishing, 2000)
The background theory and practical protocols for bioassays of biological control agents against agricultural and medical insect pests are provided. Chapters are presented on the bioassays of Bacillus thuringiensis, bacteria against soil-dwelling insect pests, entomopathogenic viruses, entomogenous fungi, microsporidia [Microspora] and entomopathogenic nematodes, statistical and computational analysis of bioassay data and legislation affecting the collection, use and safe handling of entomopathogenic microbes and nematodes.
Keywords: DD500 - Laws and Regulations; FF620 - Plant Pests, (New March 2000); HH100 - Biological Control; VV220 - Protozoan, Helminth and Arthropod Parasites of Humans, (New March 2000); VV230 - Public Health Pests, Vectors and Intermediate Hosts, (New March 2000); YY700 - Pathogens, Parasites and Infectious Diseases (Wild Animals), (New March 2000); ZZ100 - Mathematics and Statistics; ZZ390 - Microbiology (General); ZZ900 - Techniques and Methodology